Measurements of semi‐volatile organic compounds in settled dust: influence of storage temperature and duration. (19th September 2013) - Blanchard, O.; Mercier, F.; Ramalho, O.; Mandin, C.; Le Bot, B.; Glorennec, P.
Abstract Indoor dust samples cannot always be analyzed immediately after collection. However, little information is currently available on how storage conditions may affect measurements. This study was designed to determine how sample storage conditions may affect the concentration of semi‐volatile organic compounds (SVOCs) in the dust. A composite dust was prepared using a Standard Reference Material (SRM 2585) with real indoor dust samples. The composite dust was stored in various types of packaging, at different temperatures (−18°C, 5°C, 20°C, and 35°C), and in different light conditions. The concentration of SVOCs was measured after various storage durations. No effect on SVOC concentrations was observed for the composite dust stored in an amber glass vial at −18°C for 36 months. At 5°C, 20°C, and 35°C, losses occurred for the more volatile compounds. The experimental storage conditions clearly showed that temperature and duration affected the concentrations of SVOCs in the composite dust. The type of packaging material (polyethylene zip bag or polyethylene garbage bag) did not seem to have a systematic effect on the preservation of SVOCs in the composite dust. Maximum storage duration times are proposed for each compound at various temperatures. For most compounds, samples can be stored for 2 months at 20°C. For samples that cannot be analyzed immediately, we recommend to store them in the dark at −18°C to ensure a good recovery of all tested compounds.